Investigating Ocean Deoxygenation During the PETM Through the Cr Isotopic Signature of Foraminifera. Issue 6 (17th June 2019) - Remmelzwaal, Serginio R. C.; Dixon, Sophie; Parkinson, Ian J.; Schmidt, Daniela N.; Monteiro, Fanny M.; Sexton, Philip; Fehr, Manuela A.; Peacock, Caroline; Donnadieu, Yannick; James, Rachael H.
Abstract: Over the past several decades, oxygen minimum zones have rapidly expanded due to rising temperatures raising concerns about the impacts of future climate change. One way to better understand the drivers behind this expansion is to evaluate the links between climate and seawater deoxygenation in the past especially in times of geologically abrupt climate change such as the Palaeocene‐Eocene Thermal Maximum (PETM), a well‐characterized period of rapid warming 56 Ma. We have developed and applied the novel redox proxies of foraminiferal Cr isotopes (δ 53 Cr) and Ce anomalies (Ce/Ce*) to assess changes in paleoredox conditions arising from changes in oxygen availability. Both δ 53 Cr and Cr concentrations decrease notably over the PETM at intermediate to upper abyssal water depths, indicative of widespread reductions in dissolved oxygen concentrations. An apparent correlation between the sizes of δ 53 Cr and benthic δ 18 O excursions during the PETM suggests temperature is one of the main controlling factors of deoxygenation in the open ocean. Ocean Drilling Program Sites 1210 in the Pacific and 1263 in the Southeast Atlantic suggest that deoxygenation is associated with warming and circulation changes, as supported by Ce/Ce* data. Our geochemical data are supported by simulations from an intermediate complexity climate model (cGENIE), which show that during the PETM anoxia was mostly restricted to the Tethys Sea, while hypoxia was more widespread as a result of increasing atmospheric CO2 (from 1 to 6 times preindustrial values). Key Points: Chromium isotope variations in foraminifera are controlled by the local redox state Deoxygenation during the Palaeocene‐Eocene Thermal Maximum caused widespread hypoxia throughout the global oceans Ocean water warming cannot fully account for the reported extent of open ocean deoxygenation during the Paleocene Eocene Thermal Maximum